Spectral effects on the energy yield of various photovoltaic technologies in Lima (Peru) - Conde L.A. (2021)
This study presents for the first time the spectral impact on the performance of different photovoltaic (PV) technologies in Lima, Peru. We experimentally monitored the spectral distributions over one year (March 2019–February 2020). The average photon energy (APE) is calculated as a representative parameter to evaluate the spectral distributions. The spectral mismatch factor (MM) enables an estimation of the spectral gains of distinct PV technologies: amorphous silicon (a-Si), perovskite, cadmium telluride (CdTe), multicrystalline silicon (multi-Si), monocrystalline silicon (mono-Si) and copper indium gallium selenide with two distinct band-gaps (CIGS-1 and CIGS-2). We found that the annual APE has a value of 1.923 eV, indicating that the spectrum is shifted to shorter wavelengths. In contrast to studies performed in other locations, the spectral distribution shows relatively small monthly APE value variations. This nearly negligible seasonality could be attributed to the low latitude and the particular climate in Lima. Larger-bandgap PV technologies, such as a-Si, perovskite, and CdTe, resulted in annual spectral gains of +6.8%, +4.8%, and +2.1%, respectively. Lower-bandgap PV technologies (CIGS-2, multi-Si, CIGS-1, and mono-Si), present small annual spectral gains of ?0.9%, ?1.4%, ?1.6% and ?2.3%, respectively. Also, a quasi-linear correlation between APE and MM was found for all PV technologies. © 2021